The Effect of Competency and Servant Leadership on Performance with Satisfaction as a Mediating Variable (Study at KONI Semarang City) - Sugeng Dilianto; Endang Tjahjaningsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
The importance of improving performance quality in sports organizations, especially in the context of KONI as an institution that plays a major role in advancing the world of sports in Semarang City. The variables of competence, servant leadership, and job satisfaction play a crucial role in enhancing employee performance. High competence enables employees to complete tasks effectively, while servant leadership fosters a supportive work environment and increases job satisfaction. High job satisfaction will motivate employees to perform better. This study aimed to analyze the effect of competence and servant leadership on performance with satisfaction as a mediating variable (Study at KONI Semarang City). This research is a type of quantitative research. This study's population is athletes, coaches, sports branch managers, KONI managers, and employees of the Youth and Sports Service (Diaspora) of Semarang City, with as many as 250 people. The sampling technique of this study used proportionate stratified random sampling, using the Slovin formula to obtain a sample size of 154. The analysis technique of this research used Statistical Package for Social Science (SPSS) version 26 software. The results of this study indicate that competence and servant leadership have a positive and significant effect on job satisfaction. Competence, Servant leadership, and job satisfaction have a positive and significant effect on employee performance. Job satisfaction cannot mediate Competence in influencing the performance of administrators and employees at KONI Semarang City. Job satisfaction cannot mediate Servant leadership in influencing the performance of administrators and employees at KONI Semarang City.